2007
DOI: 10.1007/s11434-007-0293-y
|View full text |Cite
|
Sign up to set email alerts
|

Nickel accumulation and its effects on the survival rate of Spodoptera litura fabricius under continuous nickel stress

Abstract: The artificial diets mixed with various concentrations of nickel were offered to the larvae of the phytophagous insect Spodoptera litura Fabricius for 3 generations. Nickel accumulations in the 6th instar larvae, pupae and newly emerged adults of the corresponding generations of S. litura were investigated by Inductively Coupled Plasma-Atomic Emission Spectrometer (ICP-AES), and the effects of nickel accumulations on the survival rate of S. litura were also evaluated by individual rearing. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Evidently, Ni uptake of HI depends on the growth substrate, and this result should be further investigated. The BAF <1 for Ni agrees with the observations of Sun et al (2007) [69]: they demonstrated that pupae and adults of Spodoptera litura did not accumulate Ni. Moreover, they observed that Ni concentrations in pupae and adults were significantly lower than those in larvae, which indicated that the excessive nickel might be excreted during metamorphosis, as observed also for the other PTEs indagated.…”
Section: Nickelsupporting
confidence: 90%
“…Evidently, Ni uptake of HI depends on the growth substrate, and this result should be further investigated. The BAF <1 for Ni agrees with the observations of Sun et al (2007) [69]: they demonstrated that pupae and adults of Spodoptera litura did not accumulate Ni. Moreover, they observed that Ni concentrations in pupae and adults were significantly lower than those in larvae, which indicated that the excessive nickel might be excreted during metamorphosis, as observed also for the other PTEs indagated.…”
Section: Nickelsupporting
confidence: 90%
“…In the previous studies, we found that the survival rate of S. litura larvae fed on the diets treated with more than 5 mg/kg nickel was significantly decreased [17] , apoptosis of hemocytes of 6th instar larvae was inhibited and energetic contents in the hemolymph was reduced. Undoubtedly, the development of S. litura larvae was severely affected by higher doses of nickel (unpublished data).…”
Section: Discussionmentioning
confidence: 90%
“…Potential mechanisms for the elevated mortality of late‐instar larvae may include the accumulation of trace heavy metals in larvae by cumulative consumption (Sun et al., ), desiccation or cuticle damage as occurs with inert Diatomocaeous Earth (Korunić, ), or the cost of mandibular wear from consuming abrasive surfaces (Ennis, Mader, Burnside, Bauce, & Despland, ; Kyi, Zalucki, & Titmarsh, ). High larval mortality in the first 10 days of the experiment was likely due to (a) high background mortality of second instars that are at a more vulnerable life stage and (b) the shock of transferring from undefended and nutritionally balanced laboratory diet to relatively low‐quality leaf material and (c) intraspecific competition between neonates grouped in survival tests.…”
Section: Discussionmentioning
confidence: 99%